IMPROVING THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTION BY APPLYING THE TEAM-GAMES-TOURNAMENT TECHNIQUE - Bunga Ria Sebayang and Amrin Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study attempted to improve the students’ achievement in writing description by applying the Team-Games-Tournament Technique. This study was conducted by applying classroom action research. The subject of the research was the grade VII students of state Junior High School Swasta Laksamana Martadinata Medan. The numbers of the students were 50. The research was done into two cycles in which the first cycle consisted of three meetings and second cycle consisted of three meetings.  The instruments used in this study were writing test, interview sheet, diary note, and observation sheet. The techniques for data analysis were qualitative and quantitative. In analyzing the data, the mean of the students’ score for the pre-test was 57.6, for progressing-test I was 65.38, for progressing-test II was 74.82, and the post-test was 82.24, and the total percentage of the improvement from the pre-test into post-test was 88 %. The findings showed that the students’ score kept improving in every evaluation. It means that the application of Team-Games-Tournament Technique potentially improves the students’ achievement in writing description text.